2016
DOI: 10.3153/jaefr16014
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF DIETARY ZEOLITE LEVELS ON SOME BLOOD PARAMETERS OF GILTHEAD SEABREAM (Sparus aurata) JUVENILES

Abstract: Abstract:In this study, it was aimed to investigate the effects of dietary zeolite supplementations on blood parameters of gilthead seabream (Sparus aurata). Zeolite was gradually included into the diets at 0%, 1%, 2%, 3% and 4% and fed to triplicated groups of fish for 10 weeks. Dietary zeolite levels did not affect red blood cell, white blood cell and hemoglobin levels of sea bream. On the other hand, serum glucose levels were linearly decreased whereas triglyceride quadratically increased with zeolite level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…Jawahar et al (2016) reported that different rates of dietary zeolite level elevated triglyceride and cholesterol compared to the control group in snakehead murrel. All the researchers strongly stressed that the mechanisms behind the possible effects of dietary zeolite to blood chemistry values were still unknown (Khodanazary et al, 2013;Jawahar et al, 2016;Kanyilmaz and Tekellioglu, 2016). The current experiment showed that triglyceride and VLDL levels were highest with the addition of 1% zeolite and the lowest with the addition of 2.5% compared to the control group.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Jawahar et al (2016) reported that different rates of dietary zeolite level elevated triglyceride and cholesterol compared to the control group in snakehead murrel. All the researchers strongly stressed that the mechanisms behind the possible effects of dietary zeolite to blood chemistry values were still unknown (Khodanazary et al, 2013;Jawahar et al, 2016;Kanyilmaz and Tekellioglu, 2016). The current experiment showed that triglyceride and VLDL levels were highest with the addition of 1% zeolite and the lowest with the addition of 2.5% compared to the control group.…”
Section: Discussionmentioning
confidence: 53%
“…Khodanazary et al (2012) reported that the addition of %2.5 zeolite had no effects on serum cholesterol levels in common carp which was parallel with this experiment. Kanyilmaz and Tekellioglu (2016) stated that different rates of dietary zeolite inclusion had a significant effect on serum cholesterol and triglycerides but no effect on BUN levels of gilthead seabream. The researchers (Kanyilmaz and Tekellioglu, 2016) also stressed that the reason for the alterations in serum cholesterol and triglycerides might be originated from absorption of short-chain fatty acids by zeolites (Ly et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing industrial, agricultural and commercial activities leads to severe ecological problems and affect the organisms living in the polluted environments (Kanyılmaz et al, 2014;Kanyılmaz and Tekellioğlu, 2016). Organisms living in terrestrial and aquatic environments are often exposed to heavy metal pollution that sometimes because causing serious health problems such as cancer.…”
Section: Introductionmentioning
confidence: 99%